Do Director Networks Help Managers Forecast Better? - Schabus, Mario (The Accounting Review, 2022)
ABSTRACT I examine whether directors' superior access to information through their board network improves the accuracy of firms' forecasting. Managers may benefit from well-connected directors (i.e., board centrality) as they may have limited insight into market developments or decision-making processes of other firms beyond knowledge specific to their firm. Employing a sample of U.S.-listed companies, I separately examine the effect of within-firm variation in direct and indirect board connections on management earnings forecast accuracy. The study contributes by showing that higher-degree connections can have an economically significant effect on the accuracy of management forecasts, regardless of firms' board interlocks. Further analyses point toward well-connected directors' ability to provide managers with valuable advice in a forecasting context, which complements directors' more extensively studied role in preventing managerial expropriation. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G3; L14; M41.